Beginning HTML with CSS and XHTML : modern guide and reference - Schultz, David; Cook, Craig; SpringerLink (Online service) (Berkeley, CA : Springer, 2007)
Describes how to develop Web sites using HTML and CSS, covering such topics as XHTML, adding content, using images, building forms, scripting, and assembling pages.
Includes index.
'Learn how to create modern, standards-compliant HTML and CSS websites with no fuss'--Cover.
Keywords: HTML (Document markup language); Cascading style sheets; XHTML (Document markup language); Web sites -- Design